Nomophobia and its implication in the mental health of university students: a bibliographic review - Huepa Cubides, Paola Juliet (2025)
Mobile phones are part of the new information technologies, and their excessive use may be associated with the presence of nomophobia, which is defined as the irrational fear experienced by individuals when they are unable to use their mobile phones continuously. This fear involves various anxieties related to not receiving or sending messages, or simply not being connected to an application or social network. The aim of this study was to identify the implications of nomophobia on the mental health of university students in relation to problematic mobile phone use, through a scientific review of the literature. This literature review followed the PRISMA guidelines, with searches conducted in Google Scholar, Scopus, EBSCOhost, ProQuest, Dialnet, and Redalyc. The inclusion criteria were: articles written in Spanish, published between 2013 and 2023, addressing the relationship between nomophobia, mental health, and problematic mobile phone use in university populations. Exclusion criteria included studies focused on children, adolescents, older adults, or written in languages other than Spanish. A total of 31 scientific articles were analyzed. The main findings show that nomophobia in university students is associated with social isolation, anxiety and depressive disorders, techno-addiction, phubbing, sleep difficulties, technostress, and academic procrastination. It is concluded that there is a direct relationship between excessive mobile phone use and the presence of nomophobia, with university students being a particularly vulnerable group due to their high technological exposure and digital dependence.